Candi Prambanan: Pengelolaan Dan Potensi Persoalannya - Sugeng Riyanto (Berkala Arkeologi, 2007)
In modern archaeological theory, various views have emerged as to how archaeologists do not only know the past, but it is time to present the past in the present along with various meanings so that it is also useful for the present. For this reason, various frameworks and theories regarding Public Archeology, CRM frameworks, "Post Processual" views, legislation, and even special analyzes, such as conflict management can be used as tools and ways to answer various problems.